Infinite Element Approximation to Axial Symmetric Stokes Flow (Journal of Computational Mathematics, 2018)
We considered in [1] the finite element approximation to axial symmetric Stokes flow in a bounded domain. The problem for the flow passing an obstacle in an unbounded domain is also frequently encountered. In this paper, we are going to give approximate solutions for this problem by an approach stated in [2]. An iterative method is used to calculate the combined stiffness matrix.